Teacher-Preparation Programs and Trauma-Informed Teaching Practices: Getting Students to CHILL - Stacy Bailey (Arizona State University, 2022)
If the recent turbulent times have shown educators anything, it is that we need to be prepared to address our own and our students' social and emotional needs. However, moments of tension are not the time to start. Rather, students need to be prepared to engage in meaningful ways with skills and competencies. To achieve this state of readiness, teachers can use self-regulation strategies such as the one I call "CHILL." CHILL is an easy-to-implement five-step process designed to reduce tension in moments of crisis and create the conditions whereby students are prepared to reengage with instruction, both with the teacher and with the class. C is for Calm down, H is for Hear yourself breathe, I is for Investigate your condition, L is for Let yourself know what you need, and the second L is for Let others know what you need. Based on the unique developmental aspects of the adolescent brains, CHILL is designed to support both pre- and in-service teachers as they seek to negotiate tense classroom situations and build skills in self-regulation and resiliency. Importantly, CHILL is a strategy for de-escalation that supports students and teachers in the face of student behavioral challenges.